2012
DOI: 10.1021/jp3022908
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Subunit Interactions in the Conformational Transitions in Adult Human Hemoglobin: An Explicit Solvent Molecular Dynamics Study

Abstract: Hemoglobin exhibits allosteric structural changes upon ligand binding due to the dynamic interactions between the ligand binding sites, the amino acids residues and some other solutes present under physiological conditions. In the present study, the dynamical and quaternary structural changes occurring in two unligated (deoxy-) T structures, and two fully ligated (oxy-) R, R2 structures of adult human hemoglobin were investigated with molecular dynamics. It is shown that, in the sub-microsecond time scale, the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 42 publications
4
24
0
Order By: Relevance
“…Within 60 ns, we see that all three simulations with TIP3P and two out of three TIPS3P simulations showed a quaternary T-to-R transition. In addition to that, in their recent work Yusuff et al also see quaternary transitions using the AMBER-99SB force field [23] when starting from the T-state in two simulations at 100 ns [9]. Both results show that the spontaneous transitions are reproducible across force-fields and render us confident that our choice of force-field yields an adequate description of the transition process.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Within 60 ns, we see that all three simulations with TIP3P and two out of three TIPS3P simulations showed a quaternary T-to-R transition. In addition to that, in their recent work Yusuff et al also see quaternary transitions using the AMBER-99SB force field [23] when starting from the T-state in two simulations at 100 ns [9]. Both results show that the spontaneous transitions are reproducible across force-fields and render us confident that our choice of force-field yields an adequate description of the transition process.…”
Section: Discussionsupporting
confidence: 54%
“…the binding affinity for in one site is increased after binding in one of the other sites. The remarkable efficiency of Hb's cooperative oxygen binding gave rise to extensive experimental and theoretical work [1][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This rotation leads to a variation of the electrostatic potential at the C/D interface (Fig 5) and to the formation of contacts that reduce the possibility of β -hairpin opening (Fig 7 and S3 Table). This coupling between quaternary and tertiary structure rearrangements has been well studied, for example, in hemoglobin [40, 41]. On the other hand, looking at the tetramer( coc c ), where one chain is already in conformation o , an intermediate behaviour between the monomer and the dimer can be observed in term of FES (Figs 2D and 3).…”
Section: Discussionmentioning
confidence: 73%
“…The scenario turned out to be even more complicated when alternative quaternary structures were found for oxy-hemoglobin (Silva, Rogers & Arnone, 1992;Safo & Abraham, 2005) . Moreover, elastic network model sampling (Xu, Tobi & Bahar, 2003) and several molecular dynamics (MD) simulations, run with different force fields (Hub, Kubitzki & de Groot, 2010;Yusuff et al, 2012;Vesper & de Groot, 2013) , suggest that: (i) deoxy-hemoglobin crystal structure is very unstable in water and quickly (within 100-200 ns) converts into oxy-hemoglobin-like structures (ii) oxy-hemoglobin is well represented by a very wide ensemble of oxy-hemoglobin-like conformations instead of a few crystal structures. Nuclear magnetic resonance (NMR) (Skoog, James Holler & Crouch, 2007) experiments confirmed the second prediction (Fan et al, 2013) and showed how neither deoxy-nor oxy-hemoglobin crystal structures fit well the NMR data (Sahu et al, 2007) .…”
Section: Introductionmentioning
confidence: 99%